The methodology for assessing the level of a state’s military-economic sustainability considering national security threat evaluations - Semenenko, Oleh; Tkach, Ivan; Cherneha, Tetiana; Abramova, Maryna; Chuhui, Herman; Herasymenko, Oleh (Social Development and Security, 2025)
Purpose: to determine the country’s ability to maintain the effective functioning of the economy and defence sector in the face of threats to national security, and to develop recommendations for strengthening resilience and adaptation to crisis situations. Method: analysis; synthesis; comparison; formalization and evaluation of the material; abstraction and conjunctural analysis (thinking). Findings: identifies the main threats for Ukraine in 2025; proposes a method of threat assessment based on expert analysis according to three criteria: probability of implementation, potential impact and controllability; identifies the main indicators of the MES in seven categories: economic, military, social, infrastructural, technological, international and environmental; calculates the integral indicator of the MES. Theoretical implications: in the development of a methodology for assessing the level of military-economic stability (MES) of the state, taking into account threats to national security, which allows not only to systematise threats, calculate the integral indicator of MES, but also to improve the methodology of security studies. Paper type: theoretical, descriptive, practical, methodical.